Metal–Organic Framework MIL-101(Cr) for High-Performance Liquid Chromatographic Separation of Substituted Aromatics - Yang, Cheng-Xiong; Yan, Xiu-Ping (Analytical chemistry (Washington), 2011)
The diverse structures and pore topologies, accessible cages and tunnels, and high surface areas make metal–organic frameworks attractive as novel media in separation sciences. Here we report the slurry-packed MIL-101(Cr) column for high-performance liquid chromatographic separation of substituted aromatics. The MIL-101(Cr) packed column (5 cm long × 4.6 mm i.d.) offered high-resolution separation of ethylbenzene (EB) and xylene, dichlorobenzene and chlorotoluene isomers, and EB and styrene. The typical impurities of toluene and o-xylene in EB and styrene mixtures were also efficiently separated on the MIL-101(Cr) packed column. The column efficiencies for EB, m-dichlorobenzene, and m-chlorotoluene are 20000, 13000, and 10000 plates m–1, respectively. The relative standard deviation for five replicate separations of the substituted aromatics was 0.2–0.7%, 0.9–2.9%, 0.5–2.1%, and 0.6–2.7% for the retention time, peak area, peak height, and half peak width, respectively. The MIL-101(Cr) offered high affinity for the ortho-isomer, allowing fast and selective separation of the ortho-isomer from the other isomers within 3 min using dichloromethane as the mobile phase. The effects of the mobile phase composition, injected sample mass, and temperature were investigated. The separation of xylene, dichlorobenzene, and chlorotoluene on MIL-101(Cr) was controlled by entropy change, while the separation of EB and styrene on MIL-101(Cr) was governed by enthalpy change.